Like milk or wine: Does firm performance improve with age? - Alex Coad; Agusti Segarra; Mercedes Teruel (Max Planck Institute of Economics, 2010)
Our empirical literature review shows that little is known about how firm performance changes with age, presumably because of the paucity of data on firm age. For Spanish manufacturing firms, we analyse the firm performance related to firm age between 1998 and 2006. We find evidence that firms improve with age, because ageing firms are observed to have steadily increasing levels of productivity, higher profits, larger size, lower debt ratios, and higher equity ratios. Furthermore, older firms are better able to convert sales growth into subsequent growth of profits and productivity. On the other hand, we also found evidence that firm performance deteriorates with age. Older firms have lower expected growth rates of sales, profits and productivity, they have lower profitability levels (when other variables such as size are controlled for), and also that they appear to be less capable to convert employment growth into growth of sales, profits and productivity.
urn:nbn:de:gbv:27-20110628-131313-1
Keywords: L25; L20; 330; firm age; firm growth; LAD; financial structure; vector autoregression; Unternehmensentwicklung; Lebenszyklus; Unternehmenswachstum; Kapitalstruktur; Schätzung; Verarbeitendes Gewerbe; Spanien